Head orthosis therapy in positional plagiocephaly: longitudinal 3D-investigation of long-term outcomes, compared with untreated infants and with a control group. (3rd April 2018) - Kunz, Felix; Schweitzer, Tilmann; Große, Stephan; Waßmuth, Nina; Stellzig-Eisenhauer, Angelika; Böhm, Hartmut; Meyer-Marcotty, Philipp; Linz, Christian
Summary: Background: As there are very few long-term studies on the effects of head orthosis on deformational plagiocephaly (DP), we investigated the outcomes of patients, including facial symmetry and dental occlusion. Methods: Forty-five infants with DP [cranial vault asymmetry index (CVAI) > 3.5 per cent] were divided into two groups: one treated with head orthosis (32 infants) and another without (13 infants). Another group without head asymmetry (CVAI ≤ 3.5 per cent) served as control. Using 3D-stereophotogrammetry, cranial asymmetry was analysed using symmetry-related variables [CVAI, posterior cranial asymmetry index (PCAI), and ear offset]. Data acquisition was performed before (T1) and at the end of treatment (T2), and at the age of 4 years (T3) for the treated group and at T1 and T3 for the remaining groups. Parameters of facial symmetry and dental occlusion were assessed at T3 for infants with DP. Results: Symmetry-related variables (∆T1−T3) improved significantly more in the treated than the control group, whereas these parameters did not differ significantly between the untreated and control group. Comparing the treated and untreated groups between T1 and T3, the reduction in the asymmetry at the treated group was significantly higher for the CVAI and PCAI. In follow-up, the untreated group showed higher incidences of facial asymmetries than the treated group. Seventy-five per cent of all lateral crossbites found in patients with DP were contralateral to the posterior flattening. Limitations: Due to ethical reasons, the investigation is a non-randomized study. Parameters of facial symmetry were only assed for the treated and untreated groups. Conclusion: Head orthosis therapy in patients with DP leads to significantly better long-term outcomes. Facial asymmetries are more frequent in patients with DP who do not receive this treatment.